Microsoft Azure Compute : the definitive guide - Valiramani, Avinash (IT best practices series., 2021)
Proven best practices for success with every Azure compute service! Compute services are key to most Azure cloud solutions, but maximizing their value requires best-practice planning, design, deployment, and operations. Now, leading consultant Avinash Valiramani presents expert guidance for driving maximum value from Microsofts portfolio of Azure compute services for IaaS, PaaS, and FaaS. Drawing on his extensive work with Microsofts Azure teams, he covers Azure VMs, VM Scale Sets, App Services, Azure Virtual Desktops, Azure Container Instances, Azure Functions, Azure Batch, and other Compute services. Whatever your role in delivering efficient, scalable compute services, this deep dive will help you make the most of your Azure investment. Leading Azure consultant Avinash Valiramani shows how to: Dive deeply into the frequently used Azure Compute services to better understand how each service works Walk through configuring each compute service and its related features and options Size, price, and create Azure VMs, and deliver the right levels of redundancy and availability Use VM Scale Sets (VMSS) to integrate VMs with load balancing and autoscaling Host web applications, mobile app back ends, and REST APIs via Azure App Service Run desktops-as-a-service at scale with Azure Virtual Desktop (AVD) Easily deploy containers on demand with Azure Container Instances (ACIs) Use serverless Azure Functions to build web APIs, process streams, and manage message queues About this Book For everyone interested in Azure infrastructure, including IT/cloud admins, security specialists, developers, engineers, and others at all levels of Azure compute experience. Especially useful for experienced IT pros in mid-sized to large organizations who have deployed, operated, monitored, upgraded, migrated, or designed infrastructure services.